The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1158/1055-9965.epi-18-0576
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent Genetic Anticipation in PMS2-Associated Lynch Syndrome Families Is Explained by Birth-cohort Effect

Abstract: Background: PMS2-associated Lynch syndrome is characterized by a relatively low colorectal cancer penetrance compared with other Lynch syndromes. However, age at colorectal cancer diagnosis varies widely, and a strong genetic anticipation effect has been suggested for PMS2 families. In this study, we examined proposed genetic anticipation in a sample of 152 European PMS2 families. Methods: The 152 families (637 family members) that were eligible for analysis were mainly clinically ascertained via clinical gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A European multicentre segregation analysis that estimated CRC incidence in path_PMS2 carriers [13] demonstrated an increased incidence in carriers under 50 years of age, similar to the findings reported in the IMRC series. In a subsequent report [14] the same group confirmed that the apparent anticipation observed was a statistical artifact caused by birth cohorts. The PLSD design eliminates such artificial anticipation.…”
Section: Discussionmentioning
confidence: 80%
“…A European multicentre segregation analysis that estimated CRC incidence in path_PMS2 carriers [13] demonstrated an increased incidence in carriers under 50 years of age, similar to the findings reported in the IMRC series. In a subsequent report [14] the same group confirmed that the apparent anticipation observed was a statistical artifact caused by birth cohorts. The PLSD design eliminates such artificial anticipation.…”
Section: Discussionmentioning
confidence: 80%
“…It has been proposed that LS families show genetic anticipation, with the first cancer appearing at an earlier age in successive generations. This hypothesis is controversial [14] with some studies showing evidence that supports genetic anticipation, in particular in families with MSH2 mutations, while data from other studies indicating that such observations may be explained by other factors [15,16]. The controversy persists partly because there is inadequate evidence for a biological mechanism that could cause genetic anticipation in LS [14].…”
Section: Introductionmentioning
confidence: 99%
“…In these syndromes the genetic defect is transmitted without alterations. Partly due to the lack of generally accepted explanatory biological mechanism and a high risk of bias in this field of research, some publications suggested this observation to be the result of different forms of bias (15)(16)(17). To our knowledge, data about genetic anticipation within MEN1 families are limited to 1 study, describing a MEN1 family of 5 generations with clinical expression suggestive of anticipation (18).…”
mentioning
confidence: 99%